2008
DOI: 10.1007/s00114-008-0457-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of spawning by tropical anguillid eels around Sulawesi Island, Indonesia

Abstract: Remarkably little is known about the life histories of the many tropical anguillid eels distributed across the Indo-Pacific region, and since the Danish expedition to study eels in the region in 1928 and 1929, research on these eels has only begun again in recent years. Sampling for anguillid leptocephali in the Indonesian Seas has been carried out recently to learn about the spawning ecology and larval distributions of tropical eels there. The leptocephali of Anguilla marmorata, Anguilla bicolor pacifica, Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances. This was the case in the Danish survey (Jespersen 1942) and during recent surveys (Aoyama et al 2003;Kuroki et al 2006;Wouthuyzen et al 2009) (Fig. 6).…”
Section: Distribution and Dispersal Of Anguillid Larvaesupporting
confidence: 53%
See 1 more Smart Citation
“…The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances. This was the case in the Danish survey (Jespersen 1942) and during recent surveys (Aoyama et al 2003;Kuroki et al 2006;Wouthuyzen et al 2009) (Fig. 6).…”
Section: Distribution and Dispersal Of Anguillid Larvaesupporting
confidence: 53%
“…It has also been realized that some tropical anguillids can spawn locally over deepwater basins (Aoyama et al 2003) and that tropical eels have shorter larval durations, faster growth, and a smaller maximum larval size than temperate species (Kuroki et al 2014). So the dispersal of anguillid eel larvae can range from the retention of A. celebesensis leptocephali within the small Tomini Bay of Sulawesi Island for about 3 months (Aoyama et al 2003;Wouthuyzen et al 2009;Kuroki et al 2014) to the dispersal of European eel leptocephali all across the North Atlantic basin over more than a year (Tesch 2003;Wang and Tzeng 2000;Miller et al 2015a). Larval catches or silver eel tagging studies indicate that in addition to A. rostrata, the eels of A. japonica, A.…”
Section: Discussionmentioning
confidence: 99%
“…Spawning seasons of temperate anguillids have been roughly estimated from the timing of the downstream migrations of silver eels into the ocean (Jellyman 2003;Tesch 2003) Kleckner and McCleave 1988;Tsukamoto 1992;Tsukamoto et al 2003). The timing of spawning of tropical anguillids is much less understood, however, even though seasonal differences have been observed in the presence or size of leptocephali in the central Indonesian Seas (Wouthuyzen et al 2009) and off west Sumatra in the eastern Indian Ocean (Jespersen 1942;Aoyama et al 2007).…”
Section: -4 Seasonal Occurrence Of Leptocephalimentioning
confidence: 99%
“…Temperate anguillid eels clearly have seasonal cycles of migration and offshore spawning that result in their leptocephali being abundant in the spawning areas and larval migration routes at certain times of year. Less is known about the spawning seasons of tropical anguillids that appear to spawn at various times of the year Kuroki et al 2006a), but may have seasonal cycles of downstream migration and spawning linked to tropical monsoon cycles (Wouthuyzen et al 2009). Similarly little is known about seasonal patterns of spawning of most marine eels, but some information is available in a few areas of the world where collections have been made at multiple times of year, such as off South Africa (Castle 1968), the Sargasso Sea McCleave 1994, 2007), Gulf of Mexico (Smith 1989a), Gulf of Guinea (Blache 1977), or at least during two times of the year near Japan Minagawa et al 2007) and in the Indonesian Seas (Miller et al ,c, 2004Wouthuyzen et al 2005).…”
Section: -3 Zoogeography and Diversity Of Leptocephalimentioning
confidence: 99%
“…2014 (A. rostrata), (A. bicolor bicolor or bicolor pacifica A. marmorata) (A. mozambica) . (Daverat et al, 2006;Leander et al, 2012), (Wouthuyzen et al, 2009;Han et al, 2012), (Gagnaire et al, 2011), (Luo et al, 2013) , . A. rostrata, A. bicolor pacifica A. marmorata A. japonica .…”
Section: Rostrata)mentioning
confidence: 99%